Active Peptide AR-9 From Eupolyphaga sinensis Reduces Blood Lipid and Hepatic Lipid Accumulation by Restoring Gut Flora and Its Metabolites in a High Fat Diet–Induced Hyperlipidemia Rat - Wang, Hong; Dong, Pingping; Liu, Xin; Zhang, Zhen; Li, Huajian; Li, Yanan; Zhang, Jiayu; Dai, Long; Wang, Shaoping (Frontiers in Pharmacology, 2022)
A bioactive peptide (AR-9) was derived from active peptide of E. sinensis (APE) using ion exchange chromatography, and its structure was deconstructed by FTIR, CD spectroscopy and UHPLC-Q-Exactive-Orbitrap MS. And a high fat diet-induced hyperlipidemia model in SD rats was used to clarify the regulatory effects of AR-9 on anti-hyperlipidemia. The results demonstrated that AR-9 whose amino acid sequence was AVFPSIVGR, was a fragment of the actin protein from Blattaria insects. AR-9 decreased the levels of lipid factors in plasma and the extent of liver damage. 16S rRNA gene sequencing results indicated that AR-9 significantly increased the relative abundance of beneficial bacteria Bacteroidetes, and reduced the relative abundance of the obesity-associated bacteria Firmicutes. Moreover, AR-9 changed gut microbiota composition and increased the relative abundance of beneficial bacteria: Lactobacillus, Clostridium, Dehalobacterium, Candidatus Arthromitus. Fecal metabolomics showed that the pathway regulated by AR-9 was the “arginine biosynthesis”, in which the contents of citrulline and ornithine were significantly increased. Spearman correlation analysis revealed that the contents of ornithine and citrulline were significantly negatively correlated with obesity-related parameters and positively correlated with the gut genera (Clostridium) enriched by AR-9. Overall, our results suggested interactions between gut microbial shifts and fecal amino acid/lipid metabolism, and revealed the mechanisms underlying the anti-HL effect of AR-9. The above results not only reveal the anti-HL mechanism of AR-9, but also provide a theoretical basis for the continued development of AR-9.